PEMAKAIAN BAHASA JAWA SEBAGAI LINGUA FRANCA DI DESA PUGER WETAN, KECAMATAN PUGER, KABUPATEN JEMBER - Agustina Dewi Setyari (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2018)
Puger Wetan Village is a coastal area consisting of ethnic Javanese, Madurese, Mandar, Using, Chinese, and Arabic. The existence of multiethnic makes the connecting language becomes indispensable as a communication medium. Using the ethnographic analysis of communication, this study looked at how people in Puger Wetan Village chose the language of communication or lingua franca. Coastal communities in Puger Wetan Village use Javanese as the liaison language or lingua franca. This is due to the adaptation done by other ethnic groups in ethnic Javanese as the largest ethnic in Puger Wetan Village.